Transition of Roles as Mothers with the Ability to Care for Babies in Primiparas (HEALTH CARE: JURNAL KESEHATAN, 2024)
Role transition in primipara is a situation where a woman experiences changes, especially when she begins with the labor stage, then becomes a mother and accepts a new family member. Becoming a mother also requires preparation and ability because you will have new responsibilities to care for your child well and optimally. This study was to determine to analyze the relationship between role transitions and the ability to care for babies in primipara. The research design was correlational with a cross sectional approach. The  population was 25 primiparas wih a total sampling technique, a sample of 25 respondens. The independent variable is role transition and the dependent variable is the ability to care for a baby. The measuring instrument used is a questionnaire on each variable. Statistical analysis used Spearman's rho with α < 0.05. The research results showed that the optimal role transition was 92% and the ability to care for babies was 88% less. The results of the Spearman rho p-value statistical test: 0.516 with r: 0.136, wich mean there is no relationship between role transitions and the ability to care for babies in primipara. The mother's ability to care for the baby is less capable, especially when the baby is one month old. This requires time to adapt to the transition to motherhood. This requires time to adapt to the transition to motherhood. However, when the baby is more than one month old, the mother is able to care for the baby according to her new role. For this reason, the ability to care for a baby requires experience gained from nurses or health workers and those family to you in order to improve your abilities, especially in the first months of the transition period as a mother.            Keyword: Role transition, Ability, Baby, Primipara